2011
DOI: 10.1093/cvr/cvr337
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein-dependent up-regulation of TGF-β2 participates in the remodelling of the myxomatous mitral valve

Abstract: Our studies demonstrate for the first time that MMV are characterized by reduced levels of MT1/2 accompanied by an up-regulation of TGF-β2. In turn, increased TGF-β2 signalling induces down-regulation of aggrecanases and up-regulation of versican, two co-operating processes that potentially participate in the development of the pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 40 publications
4
52
0
1
Order By: Relevance
“…In addition of this canonical pathway, TGF-β signals also through several Smad-independent cascades such as calcium-calcineurin and MAPK pathways. Two almost simultaneous transcriptomic studies comparing myxomatous and control mitral valves revealed, for the first time, an increased expression of TGF-β2 [1] and BMP4 [2] in human MMV. Their significance in the mitral valve disease was further demonstrated by investigating the effect of these growth factors on VIC in vitro.…”
Section: Tgf-β Superfamilymentioning
confidence: 91%
See 1 more Smart Citation
“…In addition of this canonical pathway, TGF-β signals also through several Smad-independent cascades such as calcium-calcineurin and MAPK pathways. Two almost simultaneous transcriptomic studies comparing myxomatous and control mitral valves revealed, for the first time, an increased expression of TGF-β2 [1] and BMP4 [2] in human MMV. Their significance in the mitral valve disease was further demonstrated by investigating the effect of these growth factors on VIC in vitro.…”
Section: Tgf-β Superfamilymentioning
confidence: 91%
“…Until now, no molecular mechanism was proposed to explain this modification of the VIC phenotype. Recently, we [1] and another research group [2] used global transcriptomic analysis as a start-up to investigate potential pathogenic mechanisms in human idiopathic MMV. These prospective analyses have identified members of the transforming growth factor (TGF)-β superfamily, "a disintegrin and metalloprotease with thrombospondin repeats I" (ADAMTS), and a weakening of the protection against oxidative stress as potential key phases in MMV.…”
Section: Introductionmentioning
confidence: 99%
“…The study identified decreased expression of the metallothioneins 1 and 2 (MT1/2), which protect against oxidative stress, and ADAMTS-1, an abundant aggrecanase in the mitral valve leaflets that is implicated in proteoglycan degradation. 55 Subsequent in vitro silencing of the expression of metallothioneins 1 and 2 in valvular interstitial cells culture resulted in the upregulation of TGF-β2 activity and TGF-β2 secretion, with consequent downregulation of ADAMTS-1, leading to versican accumulation and remodeling of the extracellular matrix, recapitulating the features of human MVP. 55 Collectively, these findings provide an insight into the genetic basis of MVP, which is complex, highly heterogeneous, and most likely involves causative gene mutations with genetic modifier loci that influence the disease course.…”
mentioning
confidence: 99%
“…TGFβ1 has been found in calcified aortic valve cusps and promotes calcification of aortic VICs [104]. TGFβ signalling has been associated with a number of valve diseases [105][106][107] suggesting that aberrant activation/inhibition of this pathway during embryonic development may lead to valve disease later in life. Additional studies on the role of TGFβ signalling in later stages of heart valve development and adult VIC activation are required to aid in the discovery and design of new potential therapeutics for congenital heart defects and valve disease.…”
Section: Tgfβ Signalling In Cardiac Valve Developmentmentioning
confidence: 99%